2018
DOI: 10.1111/acer.13851
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor Regarding Afshar et al. (2017): Cut‐Point Levels of Phosphatidylethanol to Identify Alcohol Misuse in a Mixed Cohort Including Critically Ill Patients

Abstract: I N THIS LETTER, we briefly discuss the findings by Afshar and colleagues (2017) regarding the use of the alcohol biomarker phosphatidylethanol (PEth) to identify alcohol misuse in a mixed cohort of individuals, particularly in critically ill patients from an intensive care unit (ICU). This particular patient group as highlighted by the authors is a difficult cohort to test for the presence of an alcohol use disorder and has therefore been underresearched. We commend the authors for providing insights into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We found that the odds of PEth sensitivity were lower for those with higher BMI, consistent with two prior studies (Hahn et al, 2012; Wang et al, 2017). In addition, since PEth is formed on the surface of red blood cells, it has been suggested that red blood cell depletion may reduce PEth (Nguyen & Seth, 2018); thus, we examined hemoglobin levels. We found increased odds of PEth sensitivity with higher levels of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the odds of PEth sensitivity were lower for those with higher BMI, consistent with two prior studies (Hahn et al, 2012; Wang et al, 2017). In addition, since PEth is formed on the surface of red blood cells, it has been suggested that red blood cell depletion may reduce PEth (Nguyen & Seth, 2018); thus, we examined hemoglobin levels. We found increased odds of PEth sensitivity with higher levels of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of small studies have examined factors that might influence PEth sensitivity, including sex (Hahn et al, 2012;Stewart et al, 2014;Wurst et al, 2010), age (Cherrier et al, 2020;Hahn et al, 2012Hahn et al, , 2016b, body mass index (BMI; Wang et al, 2017), and hemoglobin level (Beck et al, 2018;Nguyen & Seth, 2018), and liver disease (Cherrier et al, 2020); we are aware of none that examined race/ethnicity, or HIV infection status. Lastly, examination of PEth sensitivity in venous versus finger-prick blood collection is needed, due to the increased risk for hemolysis and variability in blood volume and hematocrit from finger-prick blood collection (Beck et al, 2018;De Kesel et al, 2013;Kummer et al, 2016aKummer et al, , 2016b.…”
Section: Introductionmentioning
confidence: 99%